2008
DOI: 10.1016/j.placenta.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Di-(2-ethylhexyl)-phthalate Exposure Influences Essential Fatty Acid Homeostasis in Rat Placenta

Abstract: Maintaining essential fatty acid (EFA) homeostasis during pregnancy is critical for fetal development. As the organ that controls the maternal-to-fetal supply of nutrients, the placenta plays a significant role in guiding EFA transfer to the fetus. Many EFA homeostasis proteins are regulated by peroxisome proliferator-activated receptors (PPARs). The metabolites of di-(2-ethylhexyl)-phthalate (DEHP), a ubiquitous environmental contaminant, might influence EFA homeostasis via trans-activation of PPARs with subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 36 publications
4
38
2
Order By: Relevance
“…23 In the present study, the PPARγ level in nuclei was significantly increased in the DEX groups of 21-day fetuses (137.92±56.29%) and 1-dayold neonates (59.28±24.201%) compared with the respective controls (21-day: 38.47±15.70%; 1-day-old: 100.00±40.82%). Antenatal DEX administration resulted in an approximately 3.6-fold increase in PPARγ in 21-day fetuses ( Figure 7A).…”
Section: Expression Of Pparγsupporting
confidence: 51%
See 1 more Smart Citation
“…23 In the present study, the PPARγ level in nuclei was significantly increased in the DEX groups of 21-day fetuses (137.92±56.29%) and 1-dayold neonates (59.28±24.201%) compared with the respective controls (21-day: 38.47±15.70%; 1-day-old: 100.00±40.82%). Antenatal DEX administration resulted in an approximately 3.6-fold increase in PPARγ in 21-day fetuses ( Figure 7A).…”
Section: Expression Of Pparγsupporting
confidence: 51%
“…PPARs are involved in energy metabolism and mitochondrial function-related genes, including CK, during cardiac development, 23,42 although PPARγ mainly contributes to lipid metabolism in cardiomyocytes. 42 Interestingly, we found that the expression of PPARα remained low in the 21-day fetal heart, but antenatal DEX administration significantly increased PPARγ levels in the nuclei of 21-day fetal hearts.…”
Section: Discussionmentioning
confidence: 99%
“…ATPase is known to be sensitive to its lipid milieu, and both arsenic and DEHP have been reported to perturb lipid metabolism (Bhattacharjee and Pal, 2014;Muthumani and Milton, 2013;Jia et al, 2015;Xu et al, 2009). The changes in lipid contents caused by these agents may thus, explain the alterations in the enzyme activity.…”
Section: +mentioning
confidence: 99%
“…Exposure is through inhalation at the workplace, oral ingestion or injection during medical procedures. DEHP is an antiandrogen and can lead to reproductive effects (follicular atresia, inhibition of follicle-stimulating hormone activity, pre eclampsia, miscarriage, reduced estrogen, prolonged estrus and premature thelarche in various species [39,44,102,104,109,115123]) and other effects in various species [44,90,116,124127]. No detailed data exist on epigenetic effects of phthalates, but effects on imprinting have been reported.…”
Section: Some Environmental Causes Of Epigenetic Changesmentioning
confidence: 99%
“…EDCs may exert indirect, long-term effects on progeny health via effects on the placenta. The placenta is a target of EDCs [44,116,126,148153], and may be especially sensitive [153,154]. Placental function can be altered by epigenetic changes, such as loss of imprinting [155160].…”
Section: Some Environmental Causes Of Epigenetic Changesmentioning
confidence: 99%